2018
DOI: 10.1016/j.bbadis.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 and zonula occludens-1 are targets of Akt in cardiomyocytes that correlate with cardiac contractile dysfunction in Akt deficient hearts

Abstract: While deletion of Akt1 results in a smaller heart size and Akt2 mice are mildly insulin resistant, Akt1/Akt2 mice exhibit perinatal lethality, indicating a large degree of functional overlap between the isoforms of the serine/threonine kinase Akt. The present study aimed to determine the cooperative contribution of Akt1 and Akt2 on the structure and contractile function of adult hearts. To generate an inducible, cardiomyocyte-restricted Akt2 knockout (KO) model, Akt2 mice were crossed with tamoxifen-inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…This hypothesis is also supported by the reduction in phosphorylated (p)-AKT levels in the hearts of these rats (Fig. 5D) and by the association of reduced cardiac p-AKT with disrupted gap junction proteins and cardiac contractile dysfunction (Ock et al, 2018).…”
Section: Discussionmentioning
confidence: 52%
“…This hypothesis is also supported by the reduction in phosphorylated (p)-AKT levels in the hearts of these rats (Fig. 5D) and by the association of reduced cardiac p-AKT with disrupted gap junction proteins and cardiac contractile dysfunction (Ock et al, 2018).…”
Section: Discussionmentioning
confidence: 52%
“…A previous study showed that PI3K/AKT plays a crucial role in modulating Cx43 expression (Bhattacharjee et al, 2009), conveying mechanical signals to the Cx43 hemichannel and mediating its opening in osteocytes (Batra et al, 2014). Besides, Cx43 has been shown to decrease expression in the heart of AKT1 −/− /iAKT2 knockout mice, revealing that AKT plays an important role in maintaining systolic function and Cx43 protein stability (Ock et al, 2018). Inhibition of the PI3K/AKT pathway by LY294002 can reduce Cx43 expression and block the cardioprotective effect of atorvastatin (Bian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, in two insulin resistance models based on primary rat CM, lipid overload has also been demonstrated to generate functional alterations which may have implications in DCM, such as contractile dysfunction [62, 64]. The same effect on contractility was also achieved by repressing Akt1 and Akt2 expression in rat neonatal CMs [65]. High uric acid-induced insulin resistance could be reversed by an antioxidant, indicating a mechanism of insulin resistance through oxidative stress [63].…”
Section: In Vitro Disease Models Of Dcmmentioning
confidence: 99%